Alternative 'Lives Matter' formulations in online discussions about Black Lives Matter: Use, support and resistance. (May 2023) - Goodman, Simon; Tafi, Vanessa; Coyle, Adrian
Throughout its history, the Black Lives Matter (BLM) movement has elicited strong opposition that risks stifling anti-racist progress. This paper examines how support for BLM is argued about and challenged in online settings, focussing on the use of alternative 'Lives Matter' hashtags and slogans. BLM and anti-BLM material from 2020 was identified across six online platforms, which generated 1242 data items. Data were subjected to discourse analysis informed by critical discursive psychology. Arguments over the context of racism were a recurrent feature of responses to BLM-supporting posts. The analysis demonstrates the varying ways that alternative 'Lives Matter' formulations can be used to display opposition to and undermine BLM. Of these, 'All Lives Matter' was used most prominently but also 'White Lives Matter' and others. All alternatives to BLM function to obscure or deny the discrimination that Black people face, and so work to maintain the racist status quo.